1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Integral representation of Euler - Mascheroni Constant

  1. Aug 21, 2011 #1
    The definition of the Euler - Mascheroni constant, [itex]\gamma[/itex], is given as
    [tex]\gamma = \lim_{n\rightarrow\infty}\sum_{k=1}^{n}\frac{1}{k} - \ln(n)[/tex]
    or equivalently in integral form as [tex]\gamma = \int_{1}^{\infty}\frac{1}{\left\lfloor x\right\rfloor} - \frac{1}{x}\ dx[/tex]

    I saw a seeming related integral representation
    [tex]\gamma = 1 - \int_{1}^{\infty} \frac{x - \left\lfloor x\right\rfloor}{x^2}\ dx[/tex]
    but I can't seem to derive it. I was wondering if anyone can shed some light on this.
     
  2. jcsd
  3. Aug 21, 2011 #2
    The easiest way to do this is to just expand out the integral, like so:

    [tex]\begin{align}&1 - \int_{1}^{\infty} \frac{x-\lfloor x \rfloor}{x^2}\ dx \\ &= 1 - \lim_{n \rightarrow \infty} \int_{1}^{n} \frac{x-\lfloor x \rfloor}{x^2}\ dx \\ &= \lim_{n \rightarrow \infty} 1 - \sum_{k=1}^{n-1} \int_{k}^{k+1} \frac{x - k}{x^2}\ dx \\ &= \lim_{n \rightarrow \infty} 1 - \sum_{k=1}^{n-1} \left( \ln x + \frac{k}{x}\right) \Big|_{k}^{k+1} \\ &=\lim_{n \rightarrow \infty} 1 - \sum_{k=1}^{n-1} \left( \ln (k+1) - \ln k + \frac{k}{k+1} - 1\right) \\ &=\lim_{n \rightarrow \infty} 1 - \sum_{k=1}^{n-1} \left( \ln (k+1) - \ln k - \frac{1}{k+1}\right) \\ &=\lim_{n \rightarrow \infty} 1 - \sum_{k=1}^{n-1} (\ln (k+1) - \ln k) + \sum_{k=1}^{n-1} \frac{1}{k+1} \\ &= \lim_{n \rightarrow \infty} 1 - \ln n + \sum_{k=2}^{n} \frac{1}{k} \\ &=\lim_{n \rightarrow \infty} \sum_{k=1}^{n} \frac{1}{k} - \ln n = \gamma \end{align}[/tex]
     
  4. Aug 21, 2011 #3
    Hmm, that's quite a novel approach. Thank you.
     
  5. Dec 8, 2011 #4
    I think this integral is related to the Euler-Mascheroni Constant as well:

    [tex]
    \int_{0}^{\infty}{\ln{t} \, e^{-t} \, dt} = -\gamma
    [/tex]
     
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook